DISPARITAS HAKIM DALAM MENERAPKAN HUKUMAN BAGI PELAKU TINDAK PIDANA - APRIANI, TITIN (Ganec Swara, 2025)
The aim of this research is to find out the disparity between judges in applying punishment to perpetrators of criminal acts and what are the factors that cause disparity among judges in applying punishment to perpetrators of criminal acts so that they receive sentences that often have different sentences. This research is library research, namely using data in the form of books, laws, articles, journals, several cases that often occur and other literature related to the title, while the technique and data collection is by collecting various ideas, theories and concepts from various sources. literature that focuses on the comparison process between propositions, articles or other laws. The approach methods used in this research are the statutory approach, the conceptual approach and the case approach. The research results show that. Judges in handing down decisions or disparities in judges in applying sentences to perpetrators of criminal acts often have differences in decisions and punishments because there are no specific guidelines or legal certainty for judges in handing down decisions so that judges often use their own glasses based on various factors and elements that exist in society. And there are also various factors that cause the frequent occurrence of the term disparity between judges in handing down decisions.